Use of trellis graphics in the analysis of results from field experiments in agriculture - Čobanović, Katarina (Metodološki zvezki, 2007)
Trellis graphics (Becker, Cleveland, and Shyu, 1996) is a very effective method for visualizing multidimensional data sets. The basic idea behind trellis graphics is to display any of a large variety of 1-D, 2-D or 3-D statistical plot types in trellis layout of panels, where each panel displays a subset of the data for different values of one or more additional discrete or continuous conditioning variables. The data that we use for the illustration of different applications of trellis graphics are the results of a field experiment conducted at the Institute for Field and Vegetable Crops in Novi Sad in the period 1994-1998 (Čobanovič et al., 2001) with three fertilizers (nitrogen, phosphorus and potassium) in three repetitions with nine variants of wheat. In the experiment, four quantities of each fertilizer were applied (0, 50, 100, 150 kg/ha) at plots of the same size in 20 from 64 possible combinations, whereby the yield of wheat (t/ha) was the measured outcome.
Keywords: agriculture; kmetijstvo; statistične analize; statistična grafika; računalniška grafika